1985
DOI: 10.2527/jas1985.6161402x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Tenderness, Other Carcass Traits and the Effect of Crossbreeding on these Traits in Beef Cattle

Abstract: Cundiff (1985) states: "It is estimated that today about 70 percent of the calves marketed from beef cattle breeds in the United States are crossbred and that between 50 and 60 percent of the cows are crossbred. This represents a ma jor shift to crossbreeding fro m straightbreeding which prevailed into the late 1 9~ in response to research demonstrating favorable effects of heterosis (e.g. see review by Cundiff, 1970." Research results have continued to affinn this trend of increased crossbreeding. For in stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
10

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
0
8
0
10
Order By: Relevance
“…Em seus trabalhos, Slanger et al (1985) e Urick et al (1989) comentam que as características relacionadas à deposição de gordura na carcaça são as que apresentam maiores valores de heterose. Usando animais Bos taurus, Gregory et al (1994) estimaram a heterose retida na terceira geração (F 3 ) de populações compostas, concluindo que esta só foi significativa para porcentagem de gordura na carcaça, salientando a grande variabilidade que esta característica apresenta nas diferentes raças.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Em seus trabalhos, Slanger et al (1985) e Urick et al (1989) comentam que as características relacionadas à deposição de gordura na carcaça são as que apresentam maiores valores de heterose. Usando animais Bos taurus, Gregory et al (1994) estimaram a heterose retida na terceira geração (F 3 ) de populações compostas, concluindo que esta só foi significativa para porcentagem de gordura na carcaça, salientando a grande variabilidade que esta característica apresenta nas diferentes raças.…”
Section: Resultsunclassified
“…Heterose alta para marmoreio da carne foi verificada por Marshall et al (1987), ao analisarem os efeitos genéticos sobre o desenvolvimento e as características de carcaça dos novilhos Aberdeen Tabela 3 -Valores médios para composição física da carcaça de novilhos com relação à composição racial Angus e Pardo Suíço, observando que o efeito do vigor híbrido individual para marmoreio atingiu um nível de heterose de 24,9%. O alto valor da heterose observado para uma característica que reflete o acúmulo de gordura corporal também é relatado por Slanger et al (1985) e Urick et al (1989). Na Tabela 5, são apresentados os resultados referentes às características sensoriais da carne e à força necessária para cortar as fibras da carne.…”
Section: Resultsunclassified
“…shear force values and those of other muscles in the beef carcass have been reported to be: (i) 0.20-0.32 (Joseph and Connolly 1979) based on sensory panel tenderness ratings, and (ii) 0.40 (Slanger et al 1985) and 0.26-0.43 (Shackelford et al 1995) based on shear force values. (4) Researchers at the US Meat Animal Research Center (Clay Center, NE, USA) originally reported (Shackelford et al 1995) that: (i) shear force values did not accurately reflect differences among muscles in overall tenderness, and (ii) shear force value of the LD was not highly related to the shear force values of other muscles in the carcass.…”
Section: Use Of Longissimus Dorsi As An Indicator Musclementioning
confidence: 99%
“…A heterose retida foi de 9,39 e -11,36%, respectivamente, para maciez da carne avaliada pelo painel e para força de cisalhamento. Slanger et al (1985), utilizando oito raças Bos taurus e suas combinações, verificaram que o incremento do nível de heterozigose aumentou a maciez da carne. DeRouen et al (1992) acreditam que, apesar de o efeito heterótico da raça Brahman ser positivo para maciez da carne, sua inclusão em cruzamentos pode diminuir a maciez da carne, devido ao seu forte efeito genético aditivo.…”
Section: G3 Meanunclassified